A garantia do direito à convivência familiar e comunitária de crianças e adolescentes em situação de acolhimento institucional - BORGES, Jamille Guimarães (2020)
Given that institutional care is provided by law as a protection measure for children and adolescents in socially vulnerable situations, this research addresses the institutional barriers to guaranteeing the right to family and community life of minors in order to analyze the possibility of alternative measures and respect for the provisional nature of this care as a way of prioritizing family and community reintegration. It is necessary to understand the legal nature of institutional reception, its paradigms, its historical evolution in Brazil, its main principles, the consequences of its arbitrary application, the importance of the right to family and community life and the comparison of the prerogatives of law with reality. Then, an applied research is carried out, since it will use theoretical knowledge obtained in the research for a better understanding of the problems that involve the theme and elaboration of pertinent proposals, through the exploratory method, since, besides the bibliographic survey, it will be performed data analysis able to offer a better understanding of the thematic approached. Bibliographic research, based on doctrine, scientific articles, journals, electronic documents and encyclopedias was used in the search and allocation of knowledge about institutional barriers to the guarantee of the right to family and community coexistence of underprivileged children, correlating such knowledge with already existing approaches. worked by other authors. The approach to the treatment of data collection will be qualitative, as it seeks direct source, interpretation of phenomena and attribution of meanings. Questions are obtained about the profile of institutions and minors received and conclusions about the analysis performed.